The methodology of Imam al-Sadiq (peace be upon him) in the interpretation of the Noble Qur’an - a historical study. (Journal of the College of Basic Education, 2023)
The narratives of Imam al-Sadiq (peace be upon him) were distinguished by a high scientific value, and this value comes through the sources on which the Imam (peace be upon him) relied in disseminating his sciences and knowledge. The Holy Qur’an comes at the forefront of the sources from which Imam al-Sadiq (peace be upon him) drew his historical knowledge. The Holy Qur’an included historical texts spread in the multiplication of the verses, which included events and historical news.Imam al-Sadiq (peace be upon him) relied on the approach of presenting texts and narrations on the Holy Qur’an to ensure their authenticity, and this is a very important issue that gives a positive aspect to the reader regarding his interpretation (peace be upon him) of the Holy Qur’an. Where he , peace be upon him, requires that these narrations do not contradict and violate what is stated in the Noble Qur’an, here the Imam (peace be upon him) gives precedence to the Book of God over what people say, regardless of their rank. Rather, it links the historical event with the Holy Qur’an so that the recipient has a process of realizing this event through the sacred text. That is, he links the historical event with the Qur’anic text, thus giving a historical material of a scientific and ideological nature that is free of impurities.In his debates (peace be upon him), the school of Imam al-Sadiq (peace be upon him) was distinguished in his time by freedom of opinion and research, and this was one of the reasons for the spread and dissemination of Imamate knowledge, before the end of the second century Hijraa. Rather, this culture became a model for freedom of opinion and research, and all Islamic sects followed suit in theological and scientific investigations.Thus, the events and conclusions of the research revolve, reinforced by historical evidence and clear evidence that supports what the researcher has reached, and God is the guardian of success.